2019
DOI: 10.14744/nci.2019.86658
|View full text |Cite
|
Sign up to set email alerts
|

Lateral oblique approach for internal jugular vein catheterization: Randomized comparison of oblique and short axis view of ultrasound-guided technique.

Abstract: U ltrasonography is recommended and has been found superior to the classic landmark technique for central venous catheterization [1, 2]. Agency for Healthcare Research and Quality report listed ultrasound (US) guidance for placement of central venous catheters (CVC) as one of the top patient safety practices and the use of the US during catheterization was recommended by the National Institute of Clinical Excellence since 2002 [3, 4]. Ultrasound-guided central venous catheter placement decreases complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
(25 reference statements)
2
7
1
Order By: Relevance
“…The cost can further increase when the real-time technique is used as sterile ultrasound sleeves and jelly are used. This study showed no significant difference in terms of cannulation and complications, and we agreed with Ray et al that using the pre-location technique will decrease expenditures [ 20 ]. However, nothing much we can benefit from this technique if we compare it to real-time US guidance.…”
Section: Discussionsupporting
confidence: 91%
“…The cost can further increase when the real-time technique is used as sterile ultrasound sleeves and jelly are used. This study showed no significant difference in terms of cannulation and complications, and we agreed with Ray et al that using the pre-location technique will decrease expenditures [ 20 ]. However, nothing much we can benefit from this technique if we compare it to real-time US guidance.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, rotated the ultrasound probe 90°, then punctured IJV’s anterior wall using the long axis in-plane approach ( Fig 2A–2C ). Patients in the OA-IP group used the lateral oblique approach was described in the previous study [ 25 ]. Firstly, the ultrasound probe was placed parallelly to the clavicle to obtain a short-axis view of the CCA and IJV, and then the probe was rotated 45° clockwise to obtain CCA and IJV’s oblique-axis view.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in the control group will receive right IJV catheterization using the lateral oblique approach described in the previous study (20). In this group, the ultrasound probe is placed on the jugular vein at mid-neck level to capture a transverse cross-sectional image of the CCA and IJV together.…”
Section: Oblique Axis In-plane Mthodmentioning
confidence: 99%
“…The current clinical research is mainly about the comparative study of short axis method, long axis method, oblique axis method and modified methods of the above methods, in order to seek a safer and more effective ultrasound-guided IJV puncture method. A large number of studies have shown that the oblique axis method has obvious advantages compared to the long axis and the short axis methods, so it is recommended for internal jugular vein catheterization by many scholars (9,(16)(17)(18)(19)(20). In our previous research, we proposed a modified combined short and long axis method (MCSL) (11), which combines the advantages of the modified short axis out of plane approach (MSA-OOP) with the shortaxis combined long-axis method (CSLA) to accurately locate puncture needle points and visualize the entire needle body across the entire IJV catheterization (10,13).…”
Section: Introductionmentioning
confidence: 99%